(untitled) (Al-Academy, 2016)
The comedian scenes which Shakespeare has entered in some of his tragedies(Hamlet, King Lear, and Macbeth), constantly the wrath of conservative critics and theorists of Western Drama, as big violation to Aristotle’s rules of tragedy that is forbidden to insert comedian scene in tragedy. Chapter one deals with the research problem, and its significance, purpose,Boarders and the definition of Comic Relieve. Chapter two comprises the theoretical framework which has displayed Arist-Otle’s conception about the imitation way of heroes characters between tragedy and comedy, the different function of catharsis in each one. Then the research has exposed the economical and theatrical activities in London during Elizabethan age which was looked like Athena’s golden age in fifth century B.C. The research then has talked about Shakespeare’s background in drama, and found that he followed Roman playwrights in his plays structures. And it closed the chapter with getting out the indicators of theoretical framework. Chapter three includes research procedures which contains the search method, the way of choosing samples, and analyzing the samples: gravedigger in Hamlet, gatekeeper in Macbeth, and the clown in King Lear. Chapter four has covered the research results and conclusions which declare that Comic Relieve has broken the reduction of tensions in tragedy, and pushed the mind to last alert during the continuing of the play’s action